O uso do ultrassom intracoronário no auxílio ao implante de stentsconvencionais: meta-análise - Lucas Lodi Junqueira (2011)
Context: Intravascular ultrasound (IVUS) has contributed to technology improvement in interventional cardiology, but its role in percutaneous coronary interventions (PCI) is still controversial, despite several meta-analysis published so far. Conducting reviews of systematic reviews has turned to be imperative, to divide and to contrast them, trying to minimize the bias, showing the evidence to clinical decision making.Design: Systematic review followed by meta-analysis based on intention to treat. Objectives: 1) To evaluate the role of IVUS-guided PCI with bare metal stent (BMS) implantation in reducing death, non-fatal myocardial infarction (MI) and the combined outcome of major cardiovascular adverse events (MACE). 2) To analyze the results of the meta-analysis published by Parise et al., reviewing its validity and searching for possible explanations for discrepancy in the results. Data sources: Computerized search of PubMed and Embase databases and manual search in reference lists. Study selection: Randomized clinical trials published until April 2011, comparing IVUS-guided PCI with BMS implantation with angiography-guided PCI, with at least six months of follow-up, with computed relevant clinical outcomes: death, non-fatal MI and MACE. Data extraction: Two independent reviewers performed data extraction by a sensitive search, including articles that followed the inclusion criteria with adjudication by the remainder of the investigators in cases of disagreement. Results: Five studies and 1754 patients were included. Comparing both IVUS-guided and angio-guided PCI, there were no differences regarding death OR= 1.86; 95%CI= 0.88 to 3.95; p= 0.10), non-fatal MI (OR= 0.65; 95%CI= 0.27 to 1.58; p= 0.35) and MACE (OR= 0.74; 95%CI= 0.49 to 1.13; p= 0.16). Analyzing the data from the meta-analysis of Parise et al. for MACE, we observed that the Funnel Plot, the Egger Test and the Trim and Fill Test strongly suggest publication bias and the cumulative analysis by sample size inverted order and the One Study Removed Method show the strength of the small studies in a meta-analysis. Additionally, we can see great heterogeneity between the studies. Conclusions: This meta-analysis was not able to prove benefit on IVUS-guided PCI comparing with angio-guided PCI in none of the relevant clinical outcomes evaluated. Regarding the published results from Parise et al., we observed significant methodological problems. Therefore, their results should be analyzed with caution.